Dynamic Permutations (Global Journal of Computer Science and Technology, 2015)
The confidentiality integrity and authentication of anelectronic documentare necessary in many application systems The security of confidentiality integrity and authentication of an electronic document are based on nonlinear functions in which there is no directrelationship between the inputs and the outputs This means that the inputs cannot be extracted from the outputs Indeed all modern cyphers are based on the concept of substitution transposition In data encryption standard algorithm DES which consists of many functions only one nonlinear function is used in the algorithm called substitution boxes and all other functions are linear one of these linear functions is called IP initial permutation function which performs static permutations The permutations are replaced by transpositions based on predefined positions and the permutation function is used several times in DES algorithm
Keywords: confusion; diffusion; linear function; nonlinear function; static permutations; dynamic permutations; one-way functions; hash table and complexity